Pengaruh Beban Kerja, Komunikasi, Dan Lingkungan Kerja Terhadap Kinerja - Zulfi Rohmatus Sholikhah; Muhammad Imron; Mutmainah Mutmainah (Universitas Merdeka Madiun, 2022)
This study aims to examine and determine the effect of partially or simultaneously workload, communication and work environment on the performance of employees at the Kebonsari District Office, Madiun Regency. This research is anassociative research using a quantitative approach. The population in this study were all employees of the Kebonsari District Office, Madiun District Court, amounting to 30 person. The sampling technique in this study used a saturatedsample technique, where the entire population was taken as a sample. The instrument in this study used a closed questionnaire. The data analysis technique used multiple linear regression analysis, analysis of the coefficient ofdetermination (R2), hypothesis testing using t test and F test and classical assumption test with the help of the IBM SPSS Statistics Version 25 program. The results showed that: (1) Partially Workload has a significant effect on the Performance of Kebonsari District Office Employees, Madiun Regency. (2) Partially, communication has a significant effect on the performance of employees at the Kebonsari District Office, Madiun Regency. (3) Partially, the work environment has a significant effect on the performance of employees at the Kebonsari District Office, Madiun Regency. (4) Simultaneously workload, communication and work environment affect the performance of employees at the Kebonsari District Office, Madiun Regency.